Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.4 - Multiplying Polynomials - Exercise Set - Page 289: 81



Work Step by Step

$(3x+1)(3x-1)(2y+5x)$ Multiplying $(3x+1)(3x-1),$ it is in the form of $(a+b)(a-b)$ $(a+b)(a-b)= (a^{2}-b^{2})$. $(3x+1)(3x-1)= (3x)^{2}-1^{2} = 9x^{2}-1$. $(3x+1)(3x-1)(2y+5x) = (9x^{2}-1)(2y+5x)$ $=18x^{2}y+45x^{3}-2y-5x$ $=45x^{3}+18x^{2}y-5x-2y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.